Does custody law affect family behavior in and out of marriage? - René Böheim; Mario Francesconi; Martin Halla (Johannes Kepler University of Linz, Department of Economics, 2012)
We examine the effect of joint custody on marriage, divorce, fertility and female employment in Austria using individual-level administrative data, covering the entire population. We also use unique data obtained from court records to analyze the effect on post-divorce outcomes. Our estimates show that joint custody significantly reduces divorce and female employment rates, significantly increases marriage and marital birth rates, and leads to a substantial increase in the total money transfer received by mothers after divorce. We interpret these results as evidence against Becker-Coase bargains and in support of a mechanism driven by a resource redistribution that favors men giving them greater incentives to invest in marriage specific capital.
Keywords: J12; J13; J18; K36; N32; R2; 330; Divorce; Fertility; Bargaining; Intrahousehold Allocations; Austria